The influence of the selected factors on the financial liquidity of the enterprises quoted on the NewConnect market = Wpływ wybranych czynników na płynność finansową przedsiębiorstw notowanych na rynku NewConnect - Jędrzejczak-Gas, Janina (Zielona Góra: Faculty of Economics and Management Press)
It is for evaluation of the financial liquidity that financial liquidity ratios are applied; in particular the current ratio, which is a relation of current assets to current liabilities. However, this indicator does not provide wide interpretative possibilities in synthetic terms. It is a structural system, which is called "a pyramid of indicators", that provides much greater interpretative possibilities and allows for determining. The purpose of this article is to present a proposal of a system of factors shaping the financial liquidity and to examine the strength and the influence direction of these factors on the financial liquidity of the companies quoted on the NewConnect stock exchange and ranked among construction companies.
Keywords: płynność finansowa; analiza korelacji; analiza regresji; financial liquidity; correlation analysis; regression analysis